ANALYSIS OF ANALGESIC GROUPS IN PHARMACEUTICAL PREPARATIONS USING UV SPECTRO - Mardiana, Siti Arina; Friantina, Delta Happy; Achmad, Syarifa Risqina; Fikasari, Ema Aulia; Putri, Zalfa Zahiyah; Tambunan, Prillya Posma Meldawati (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
Supervision and quality inspection of pharmaceutical preparations is carried out to ensure that the ingredients in medicinal preparations have the specified quality and quantity and follow standard analysis procedures. One form of medication is generic mefenamic acid tablets. To determine the mefenamic acid content of tablets, the ultraviolet spectrophotometric method can be used. Before performing assay analysis, the analytical method must be validated to ensure that the method meets the requirements for use. The aim of this study was to determine the validity of the ultraviolet spectrophotometry method for evaluating the determination of mefenamic acid levels in generic tablets based on certain parameters. This research is descriptive and validates the ultraviolet spectrophotometry method. Monitoring and quality inspection of pharmaceutical preparations is carried out to ensure that the ingredients in medicinal preparations have the specified quality and quantity and follow standard analysis procedures.